THE NEED FOR SCIENTIFIC CREATIVITY IN FORMING PROFESSIONAL MOBILITY IN FUTURE EDUCATORS (TAMADDUN NURI JURNALI, 2024)
This article focuses on the importance and necessity of research work in the process of formation of professional mobility of future pedagogues. The article focuses on the nature of professional mobility, its place and tasks in pedagogy. Also, ways to develop the professional mobility of future pedagogues by involving them in scientific and creative activities were analyzed. The need to improve the professional skills of future pedagogues through the study and application of scientific research, innovative solutions and pedagogical experiences is justified. The article provides the necessary conditions, resources and pedagogical recommendations for the development of professional mobility